Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Factor $z^7-1$ into linear and quadratic factors and prove that $$ \cos(\pi/7) \cdot\cos(2\pi/7) \cdot\cos(3\pi/7)=1/8$$

I have been able to prove it using the value of $\cos(\pi/7)$. Given here http://mathworld.wolfram.com/TrigonometryAnglesPi7.html

share|improve this question
add comment

4 Answers 4

Let $z=e^{\frac{i\pi}{7}}$. Then $\cos (\frac{\pi}{7})=(z+z^{-1})/2$, $\cos (\frac{2\pi}{7})=(z^2+z^{-2})/2$, $\cos (\frac{3\pi}{7})=(z^3+z^{-3})/2$. This should get you started.

share|improve this answer
add comment

Factor $x^7-1$ in $\Bbb C$ and obtain its factorization in $\Bbb R$ by pairing off conjugate roots.

share|improve this answer
add comment

$$z^7=1=e^{2n\pi i}$$ where $n$ is any integer

$$\implies z=e^{\frac{2n\pi i}7}$$ where $n=0,\pm1,\pm2,\pm3$

So, the roots of $$\frac{z^7-1}{z-1}=0\iff z^6+z^5+\cdots+z+1=0\quad(1)$$ are $e^{\frac{2n\pi i}7}$ where $n=\pm1,\pm2,\pm3$

As $z\ne0,$ divide either sides by $z^3$ to get $$z^3+\frac1{z^3}+z^2+\frac1{z^2}+z+\frac1z+1=0\quad(2)$$

Now using Euler Formula, $\displaystyle z+\frac1z=e^{\frac{2n\pi i}7}+e^{-\frac{2n\pi i}7}=2\cos\frac{2n\pi }7$ where $n=1,2,3$

Again, $$\displaystyle z^2+\frac1{z^2}=\left(z+\frac1z\right)^2-2\text{ and }z^3+\frac1{z^3}=\left(z+\frac1z\right)^3-3\left(z+\frac1z\right)$$

Put the values of $\displaystyle z^2+\frac1{z^2},z^3+\frac1{z^3}$ in $(2)$ to form a Cubic Equation whose roots are $\displaystyle2\cos\frac{2n\pi }7$ where $n=1,2,3$

Now apply Vieta's formula

share|improve this answer
    
The Equation $(1)$ is called Reciprocal Equation See math.stackexchange.com/questions/403025/… and math.stackexchange.com/questions/480102/… –  lab bhattacharjee Jan 15 at 5:24
add comment

Let $$\alpha_1 = \cos(2\pi/7), \alpha_2 = \cos(4 \pi/7), \alpha_3 = \cos(6 \pi/7)$$

Then $$ z^7-1 = (z-1) (z^2- 2 \alpha_1 z + 1)(z^2- 2 \alpha_2 z + 1)(z^2- 2 \alpha_3 z + 1)$$

Differentiate both sides and set $z=1$ to get your answer.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.